Memória em tempos de pós-guerras : um estudo das relações identitárias em contexto de crise em “O gigante enterrado” e “Um artista do mundo flutuante”, de Kazuo Ishiguro - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
An analysis of the novels The Buried Giant (2015) and An Artist of the Floating World (2018), by the renowned British writer Kazuo Ishiguro. The central themes addressed here are those of memory and forgetting in the narrative. Forgetting as an important constituent of the narrative, as well as the characters' memories and their identity and traumatic relationship. These novels reveal human dramas and discuss the ephemeral nature of life. In An Artist of the Floating World, the narrator and protagonist, Masuji Ono, is a man of his time. Renowned painter, while still young, he challenged his father to follow his artistic vocation and, during his creative development, he struggled against the shackles of traditional Japanese art to give way to a propaganda production at the service of the country. Especially throughout World War II. Using the influence he enjoyed with the authorities of the imperial government. Ono sought to help people and the less fortunate. This portrait of the artist as an old man reveals the life of a retired Masuji. As Japan rebuilds its cities after the destruction of the war and people try to move forward by looking to the future. Ono spends his days taking care of the garden, his grandson and his daughters, spending the night drinking with old friends. An Artist of the Floating World is also a novel that portrays old age its arrival and the main dramas faced. The Buried Giant is the other novel worked on in this dissertation. At a time when myth and history are two sides of the same coin, Britain is in ruins, marked by recent wars between Britons and Saxons and the fall of King Arthur. The population, orphaned and bewildered, is exposed to the most diverse threats, from ogre invasions to a mysterious mist that sinks the past into oblivion. When Axl and Beatrice decide to leave in search of their son, they don't remember his face, the last time they saw him. The elderly couple will meet Sir Gawain and other knights left over from the Arthurian era, engage in the search for a dragon that seems to be linked to the mist, and will have their love questioned, after all, is affection still strong enough when they can no longer remember the joys and sadness we've shared over the years? The research investigates the theory of memory, emphasizing its opposition: forgetting, which is something inevitable because of our condition of transience and conflict with the passage of time. However, at times, forgetting can be seen as something positive, as is the case in one of Kazuo Ishiguro's novels, The Giant Buried in a Medieval Narrative about a fog of oblivion that hangs in what is now England. In addition to this novel, he also researches An Artist of the Floating World that approaches memory, however, from the perspective of a Japanese character who survived World War II. The theoretical foundation is based on theorists, such as: Éclea Bosi (1979), Saint Augustine (1980), Harald Weinrich (2001), Joël Candau (2016), Aleida Assmann (2018), among others.
Memory in post-war times : a study of identity relations in the context of crisis in “The buried giant” and “An artist of the floating world”, by Kazuo Ishiguro
Keywords: Memória; Esquecimento; Identidade; Kazuo Ishiguro; Memory; Forget fulness; Old age; Identity; Kazuo Ishiguro; LETRAS::LITERATURAS ESTRANGEIRAS MODERNAS